Photoredox Catalysis of Cyclometalated IrIII Complex for the Conversion of Amines to Fluorinated Alkyl Amides. Issue 8 (19th June 2018) - Ng, Chi‐On; Feng, Hua; Cheng, Shun‐Cheung; Xiao, Yelan; Lo, Larry Tso‐Lun; Ko, Chi‐Chiu
Abstract: Using luminescent cyclometalated Ir III complex as photocatalyst, a new visible‐light induced photocatalytic method for the preparation of perfluorinated alkyl amides under a mild condition has been developed. Primary aliphatic, secondary aliphatic and aromatic amines as well as perfluoroalkyl iodides and bromides can be used as the substrates in the photocatalytic reactions. On the basis of the emission quenching study and the characterizations of the reaction intermediates, the mechanism of the photocatalysis has been proposed. Abstract : Preparation Iridium : With the use of luminescent cyclometalated Ir III complex, a new visible‐light induced photocatalytic method for the preparation perfluorinated alkyl amides under a mild condition has been developed. With the emission quenching study and the characterization of the reaction intermediates, the mechanism of the photocatalysis has been proposed.